From Science to Policy and Society: Enhancing the Effectiveness of Communication - Mea, Marianna; Newton, Alice; Uyarra, Maria C.; Alonso, Carolina; Borja, Angel (Frontiers in Marine Science, 2016)
Dissemination is now acknowledged as an important component of the research process, in particular for European Union (EU) funded research projects. This article builds on the authors’ experience during the EU project DEVOTES (DEVelopment Of innovative Tools for understanding marine biodiversity and assessing good Environmental Status) and aims to assist other scientists to develop a successful dissemination strategy to communicate project achievements. We provide a critical review of the different tools used for outreach to our target audiences, from the academia to the policy makers, and the general public, and try to assess their impact. An effective dissemination strategy and plan should have a clear objective, be designed before the start of the project, identify the target groups and define the methods or tools to be used according to target groups and objectives. The DEVOTES dissemination strategy included two complementary approaches of communication with stakeholders: (i) traditional (e.g. peer reviewed publications, stakeholders workshops and participation in scientific conferences), and (ii) new (e.g. social networks, smartphone applications) media tools. For each dissemination approach, we defined production targets (e.g. number of articles to be published, individual visitors on the website, etc.) to be achieved by the end of the project, and impact measurements (e.g., citation indices for peer reviewed articles) to monitor the successful implementation of DEVOTES Dissemination. This allowed us to identify which tools had been more (e.g. website) or less useful and relevant (e.g. Facebook) during the project. We conclude that impact measurements cannot be easily identified for all dissemination actions. However, for those that were possible, the DEVOTES dissemination targets were successfully achieved. Overall, the use of the tools and activities outlined in this article, combined with the constant evaluation of the dissemination goals throughout the project duration and the assessment of the effectiveness of the different tools, is essential for the achievement of an effective and timely communication of research results.